2023
DOI: 10.4102/sajpsychiatry.v29i0.2127
|View full text |Cite
|
Sign up to set email alerts
|

Mental health education for physiotherapists: A scoping review

Marilyn Hooblaul,
Thayananthee Nadasan,
Olagbegi M. Oladapo

Abstract: Background: Physiotherapists play an integral role in the management of people living with a mental illness, yet little is known about their knowledge, attitudes and perceptions about mental health globally and particularly in South Africa.Aim: The purpose of the study is to map global evidence on mental health education for physiotherapists, including their knowledge, attitude and perceptions, with the goal of using this information to design an improved undergraduate curriculum for physiotherapy in South Afr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“… 30 Physiotherapists are allied health professionals who could potentially play a role within mental healthcare services in our setting and assist with physical activity interventions. 31 , 32 However, a review of mental health policies in sub-Saharan Africa found that their importance in this context remains largely neglected. 31 This is echoed not only by the dearth of research in sub-Saharan Africa regarding the role of physical activity in mental illness but also by the lack of priority that it has been given in mental health policies, where less than 10% even make reference to physical activity recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 30 Physiotherapists are allied health professionals who could potentially play a role within mental healthcare services in our setting and assist with physical activity interventions. 31 , 32 However, a review of mental health policies in sub-Saharan Africa found that their importance in this context remains largely neglected. 31 This is echoed not only by the dearth of research in sub-Saharan Africa regarding the role of physical activity in mental illness but also by the lack of priority that it has been given in mental health policies, where less than 10% even make reference to physical activity recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…The recommendation by the authors of this review was therefore that the current South African physiotherapy curriculum be reviewed and improved to include sufficient mental health content so that ultimately physiotherapists may be better equipped to offer services to PWMI. 32 …”
Section: Discussionmentioning
confidence: 99%